Characterization of FBA genes in potato (Solanum tuberosum L.) and expression patterns in response to light spectrum and abiotic stress - Li, Ting; Hou, Xinyue; Sun, Zhanglun; Ma, Bin; Wu, Xingxing; Feng, Tingting; Ai, Hao; Huang, Xianzhong; Li, Ruining (Frontiers in Genetics, 2024)
Fructose-1, 6-bisphosphate aldolase (FBA) plays vital roles in plant growth, development, and response to abiotic stress. However, genome-wide identification and structural characterization of the potato (Solanum tuberosum L.) FBA gene family has not been systematically analyzed. In this study, we identified nine StFBA gene members in potato, with six StFBA genes localized in the chloroplast and three in the cytoplasm. The analysis of gene structures, protein structures, and phylogenetic relationships indicated that StFBA genes were divided into Class I and II, which exhibited significant differences in structure and function. Synteny analysis revealed that segmental duplication events promoted the expansion of the StFBA gene family. Promoter analysis showed that most StFBA genes contained cis-regulatory elements associated with light and stress responses. Expression analysis showed that StFBA3, StFBA8, and StFBA9 showing significantly higher expression levels in leaf, stolon, and tuber under blue light, indicating that these genes may improve photosynthesis and play an important function in regulating the induction and expansion of microtubers. Expression levels of the StFBA genes were influenced by drought and salt stress, indicating that they played important roles in abiotic stress. This work offers a theoretical foundation for in-depth understanding of the evolution and function of StFBA genes, as well as providing the basis for the genetic improvement of potatoes.